Challenges and science-based implications for modern management and conservation of European ungulate populations - Apollonio, Marco; Belkin, Vladimir; Borkowski, Jakub; Borodin, Oleg; Cagnacci, Francesca; Danilkin, Aleksey; Danilov, Peter; Faybich, Andrey; Ferretti, Francesco; Gaillarc, Jean Michel; Hayward, Matt; Heshtaut, Pavel; et al. (Springer, 2017)
Wildlife management systems face growing challenges to cope with increasingly complex interactions between wildlife populations, the environment and human activities. In this position statement, we address the most important issues characterising current ungulate conservation and management in Europe. We present some key points arising from ecological research that may be critical for a reassessment of ungulate management in the future.
Keywords: population sustainability; science-based management; ekosysteemit; populaatiot; hirvieläimet; Cervidae; ecosystems; population ecology; wildlife management